Satire: Sindiran Humor dalam Naskah Drama Arab - Tamim Mulloh; Ade Destri Deviana; Muhammad Ridho Naufal (Mantiqu Tayr: Journal of Arabic Language, 2024)
The Arabic drama "Mismaru Juha" by Ali Ahmad Bakatsir has the character Sheikh Juha that has a role by the humorous and wise. The Arabic drama used script with Arabic language for Sheikh Juha is full of critical of elites allied with other nations. It is according the writer has nationalism. Critical of drama script expressed in stylistic satire, namely an expression of humorous allusion. The aim of this research is to determine the type of satire of drama script Mismaru Juha and its percentage. The method uses a descriptive-qualitative type of library research, with the focus of the study being the overall style of satirical language in drama texts Arabic of drama script Mismaru Juha. There are four stages of data analysis are organizing data, reducing data, presenting data, and drawing conclusions. The result is the Arabic drama used satire style in the form of humor to give criticm based on norms society. The satire is three types are: (1) horatian satire (soft allusion and empathy) with 45%; (2) Juvenalian satire (allusion harsher than horizontal satire, direct criticism) with 25%; and (3) Manippean satire (allusion of narrative with stories or experiences that have occurred) with 30%. The type of satire that is more often used is horation satire that has humor, polite speech andnot rude words.